2007
DOI: 10.1097/01.phh.0000296142.79423.e8
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Finances for Public Health System Improvement

Abstract: Reforming the public health infrastructure requires substantial system changes at the state level; state health agencies, however, often lack the resources and support for strategic planning and systemwide improvement. The Turning Point Initiative provided support for states to focus on large-scale system changes that resulted in increased funding for public health capacity and infrastructure development. Turning Point provides a test case for obtaining financial and institutional resources focused on systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…That study also showed that states were able to leverage $2 for every $1 of CDC funding, demonstrating the effectiveness of CDC resources in state-level obesity prevention efforts ( 8 ). These findings are similar to those from other obesity prevention infrastructure initiatives that demonstrated the effectiveness of partnerships in leveraging additional funding ( 9 ). Other program evaluations describe the critical role of state health departments in supporting and strengthening community-based obesity prevention by providing technical assistance, resources, and evaluation ( 10 ).…”
Section: Introductionsupporting
confidence: 83%
“…That study also showed that states were able to leverage $2 for every $1 of CDC funding, demonstrating the effectiveness of CDC resources in state-level obesity prevention efforts ( 8 ). These findings are similar to those from other obesity prevention infrastructure initiatives that demonstrated the effectiveness of partnerships in leveraging additional funding ( 9 ). Other program evaluations describe the critical role of state health departments in supporting and strengthening community-based obesity prevention by providing technical assistance, resources, and evaluation ( 10 ).…”
Section: Introductionsupporting
confidence: 83%
“…8 Survey findings indicated that grantees leveraged, on average, six times the total investment provided by the RWJF to the 17 Turning Point states participating in this research and that these funds came from numerous public and private sources. This preliminary inquiry demonstrated that several states had leveraged significant resources and initiated in-terest in conducting a more formal study.…”
Section: The Turning Point Initiativementioning
confidence: 99%